Regionally specific levels and patterns of keratin 8 expression in the mouse embryo visceral endoderm emerge upon anterior-posterior axis determination - Despin-Guitard, Evangéline; Quenec’Hdu, Ronan; Nahaboo, Wallis; Schwarz, Nicole; Leube, Rudolf E.; Chazaud, Claire; Migeotte, Isabelle (Frontiers in Cell and Developmental Biology, 2022)
The mechanical properties of the different germ layers of the early mammalian embryo are likely to be critical for morphogenesis. Cytoskeleton components (actin and myosin, microtubules, intermediate filaments) are major determinants of epithelial plasticity and resilience to stress. Here, we take advantage of a mouse reporter for Keratin 8 to record the pattern of the keratin intermediate filaments network in the first epithelia of the developing mouse embryo. At the blastocyst stage, Keratin 8 is strongly expressed in the trophectoderm, and undetectable in the inner cell mass and its derivatives, the epiblast and primitive endoderm. Visceral endoderm cells that differentiate from the primitive endoderm at the egg cylinder stage display apical Keratin 8 filaments. Upon migration of the Anterior Visceral Endoderm and determination of the anterior-posterior axis, Keratin 8 becomes regionally distributed, with a stronger expression in embryonic, compared to extra-embryonic, visceral endoderm. This pattern emerges concomitantly to a modification of the distribution of Filamentous (F)-actin, from a cortical ring to a dense apical shroud, in extra-embryonic visceral endoderm only. Those regional characteristics are maintained across gastrulation. Interestingly, for each stage and region of the embryo, adjacent germ layers display contrasted levels of keratin filaments, which may play a role in their adaptation to growth and morphological changes.